Mata Uang Kripto Sebagai Mahar Perkawinan Perspektif Maqāṣid Al-Syarī‘Ah Jasser Auda - Hirza, Ghifari; Hasan, Sudirman; Rouf, Abd. (Maqasid: Jurnal Studi Hukum Islam, 2025)
Amid the advancement of technology and the digital economy, cryptocurrency has begun to attract attention as an alternative form of dowry (mahr). However, its use remains controversial. The Indonesian Ulema Council (MUI) prohibits cryptocurrency as a means of payment due to elements of garar (uncertainty), ḍarar (harm), and qimār (speculation/gambling). On the other hand, the Commodity Futures Trading Regulatory Agency (Bappebti) and the Financial Services Authority (OJK) recognize cryptocurrency as a legal commodity for trading. This research aims to describe the legitimacy of using cryptocurrency as dowry in marriage in Indonesia and analyze it based on maqāṣid al-syarī‘ah according to Jasser Auda. This is a normative legal research using a conceptual approach. Data was collected through literature studies, including primary, secondary, and tertiary legal materials, as well as relevant non-legal sources. The analysis is conducted qualitatively by interpreting the legal materials obtained.The research findings show: First, from the perspective of positive law, cryptocurrency is recognized as a legitimate commodity, although not a legal tender. In Islamic law, cryptocurrency can be used as dowry as long as it has clear value, is mutually agreed upon, and is free from prohibited elements. To overcome volatility, asset-backed crypto or conversion to official currency can be used. Second, based on Jasser Auda’s systems theory, cryptocurrency can be accepted as dowry if it meets the principles of maqāṣid al-syarī‘ah, such as justice, public benefit, and mutual agreement, and is conducted transparently through regulated platforms.